1997
DOI: 10.4141/s96-004
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mineralization and availability in manure composts from Québec biological farms

Abstract: N'Dayegamiye, A., Royer, R. and Audesse, P. 1997. Nitrogen-mineralization and availability in manure composts from Québec biological farms. Can. J. Soil Sci. 77: 345-350. The real contribution of composts to N availability depends on their characteristics and maturity. A laboratory incubation experiment (140 d) was conducted parallel to a greenhouse study (330 d) in a split-split-plot design, with, respectively, two peat rates (0, 20 g kg -1 soil), five manure composts and four compost rates (0, 250, 500 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Much of the N uptake in the initial cycle was presumably from inorganic N already present in the amendments, as observed in earlier studies (N'Dayegamiye et al 1997;Dao and Cavigelli 2003;Han et al 2004;Yang et al 2004).…”
Section: Nitrogen Dynamic Releasesupporting
confidence: 67%
See 1 more Smart Citation
“…Much of the N uptake in the initial cycle was presumably from inorganic N already present in the amendments, as observed in earlier studies (N'Dayegamiye et al 1997;Dao and Cavigelli 2003;Han et al 2004;Yang et al 2004).…”
Section: Nitrogen Dynamic Releasesupporting
confidence: 67%
“…Soil-incorporated composted manures can provide supplemental N for crop growth (Fortuna et al 2003;Larney et al 2003), however, the N mineralization rates among different composts can vary significantly (Gagnon and Simard 1999;Hadas and Portnoy 1994;N'Dayegamiye et al 1997). Mineralized N is generally less from composted than from fresh manure (Lynch et al 2004;Tyson and Cabrera 1993), particularly where N immobilization with fresh-manure incorporation is negligible.…”
Section: Mots Clésmentioning
confidence: 99%
“…Good indicators of potential N mineralization include soluble organic carbon and insoluble organic carbon (Hadas and Portnoy 1994), C:N ratio of manure (Qian and Schoenau 2002a), and Walkley-Black N (Douglas and Magdoff 1991). N'Dayegamiye et al (1997) found that most of the manures and composts studied had high N mineralization rates until labile forms of N from microbial products were exhausted, followed by a period of slow mineralization of more stable N forms. Nutrient release may be synchronous with crop needs resulting in more efficient N utilization (Ma et al 1999).…”
mentioning
confidence: 99%
“…Nutrient release from manures and composts can be quite variable ranging from 10 to 40% of total N (N tot ) (Castellanos and Pratt 1981;Hadas and Portnoy 1994;N'Dayegamiye et al 1997;Qian and Schoenau 2002a). Good indicators of potential N mineralization include soluble organic carbon and insoluble organic carbon (Hadas and Portnoy 1994), C:N ratio of manure (Qian and Schoenau 2002a), and Walkley-Black N (Douglas and Magdoff 1991).…”
mentioning
confidence: 99%
“…It has been demonstrated that the amount of N mineralized is related to manure type, material composition, degree of maturity, application rate and soil type (Castellanos and Pratt 1981;Leclerc et al 1986;Hébert et al 1991;N'Dayegamiye et al 1997;. The intensity of composting management had only a positive impact when materials were welldecomposed (Shi et al 1999).…”
Section: Mots Clés: Compostage Fumier De Ferme Composition Du Solmentioning
confidence: 99%